MIA SH3 Domain ER Export Factor 3 Deficiency Prevents Neointimal Formation by Restoring BAT-Like PVAT and Decreasing VSMC Proliferation and Migration - Lei, Yu; Xu, Jianfei; Li, Mengju; Meng, Ting; Chen, Meihua; Yang, Yongfeng; Li, Hongda; Zhuang, Tao; Zuo, Junli (Frontiers in Endocrinology, 2021)
Abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) and excessive accumulation of dysfunctional PVAT are hallmarks of pathogenesis after angioplasty. Recent genome-wide association studies reveal that single nucleotide polymorphism (SNP) in MIA3 is associated with atherosclerosis-relevant VSMC phenotypes. However, the role of MIA3 in the vascular remodeling response to injury remains unknown. Here, we found that expression of MIA3 is increased in proliferative VSMCs and knockdown of MIA3 reduces VSMCs proliferation, migration and inflammation, whereas MIA3 overexpression promoted VSMC migration and proliferation. Moreover, knockdown of MIA3 ameliorates femoral artery wire injury-induced neointimal hyperplasia and increases brown-like perivascular adipocytes. Collectively, the data suggest that MIA3 deficiency prevents neointimal formation by decreasing VSMC proliferation, migration and inflammation and maintaining BAT-like perivascular adipocytes in PVAT during injury-induced vascular remodeling, which provide a potential therapeutic target for preventing neointimal hyperplasia in proliferative vascular diseases.